Biometrics for Hardware Security and Trust: Discussion and Analysis - Sengupta A.; Rathor M.; Chaurasia R. (My University, 2025)
Ensuring hardware security and trust is not only important for securing the designer's/owner's revenue but also for his/her reputation and trust in the electronics market. Biometrics-based authentication is an emerging approach to ensure security and trust in hardware, as it offers a unique identification of the true hardware designer/owner. This article provides a novel discussion and analysis of recently employed biometric techniquesâ intellectual property (IP) fingerprint, facial, and palmprinta for hardware IP security. More explicitly, this article discusses the potential hardware security threats, followed by a discussion of existing techniques for security. Furthermore, the article also provides a design flow for the IP core fingerprint biometrics, IP facial biometrics, and IP palmprint biometrics along with their corresponding detection flows. Finally, the article provides an analysis of the hardware security strength achieved through different biometric techniques in terms of probability of coincidence. © 2023 IEEE.